Poly (vinylpyrrolidone)-Grafted Silica as a Polymeric Cosolvent Catalyst for Organic Transformations in Organic and Aqueous Media - S. Ghasemi; B. Tamami; R. Teymoori; H. Allahyari (Journal of Sciences, Islamic Republic of Iran)
Poly (vinylpyrrolidone)-grafted silica as an organic-inorganic hybrid material was used as an effective heterogeneous polymeric cosolvent catalyst in organic reactions. This modified silica catalyzed nucleophilic displacement of alkyl halides for easy preparation of alkyl thiocyanates, alkyl cyanides, alkyl azides and alkyl aryl ethers. Furthermore, the catalyst was applied for the conversion of epoxides to thiranes, thiocyanohydrins and azidohydrins. These reactions were performed in acetonitrile and aqueous media to produce the corresponding products in high yields and short reaction times. The catalyst can be recovered and reused several times.